PERTANGGUNGJAWABAN DIREKSI BUMN TERHADAP KEPUTUSAN BISNIS YANG MERUGIKAN PERUSAHAAN BERDASARKAN PRINSIP BUSINESS JUDGEMENT RULE - Daffa, Rofi Aisy (Ensiklopedia Education Review, 2025)
Abstract: This study discusses the accountability of the board of directors of State-Owned Enterprises (SOEs) for business decisions that result in corporate losses, by examining the application of the Business Judgment Rule (BJR) principle. This principle asserts that directors cannot be held legally liable for corporate losses as long as the decisions were made in good faith, with due care, free of conflicts of interest, and in line with the company's objectives. However, in the context of SOEs particularly those in the form of Persero there is regulatory overlap between the Limited Liability Company Law, the SOE Law, and the Anti-Corruption Law. This overlap creates legal uncertainty in distinguishing between business risk and criminal conduct. This study highlights the case of Karen Agustiawan, former President Director of PT Pertamina (Persero), who was convicted for making an investment decision without adequate due diligence, which was deemed detrimental to state finances. Normatively, the assets of Persero SOEs are corporate assets separate from the state, and thus any losses should be resolved through corporate mechanisms rather than criminal prosecution. Therefore, regulatory harmonization is needed to prevent the criminalization of directors based on business risks. This research uses a normative approach and case study as its method of analysis.Keywords: Business Judgment Rule, SOEs, Board of Directors, Accountability